2008
DOI: 10.3843/biodiv.4.3:4
|View full text |Cite
|
Sign up to set email alerts
|

Status of a protected area system in the Hindu Kush-Himalayas: An analysis of PA coverage

Abstract: SUMMARYMultifaceted patterns of protected area (PA) expansion are reviewed considering: i) the increase in PA number and coverage; ii) distribution and extent of important bird areas (IBAs); and iii) distribution and coverage of global biodiversity hotspots and the Global 200 Ecoregions that fall within the Hindu Kush-Himalayas (HKH). The analysis revealed that biodiversity conservation is a priority for the eight regional member countries of the HKH, who have established 488 PAs over the last 89 years (1918 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 42 publications
0
60
0
Order By: Relevance
“…Forests are the main source of timber and fuel wood, and also a major source of fodder for livestock. Nepal is home to 35 forest types, 75 vegetation types and 118 ecosystems, along with four global biodiversity hotspots (Chettri et al 2008). However, these ecosystems are facing challenges due to natural and anthropogenic induced climate change.…”
Section: Study Areamentioning
confidence: 99%
“…Forests are the main source of timber and fuel wood, and also a major source of fodder for livestock. Nepal is home to 35 forest types, 75 vegetation types and 118 ecosystems, along with four global biodiversity hotspots (Chettri et al 2008). However, these ecosystems are facing challenges due to natural and anthropogenic induced climate change.…”
Section: Study Areamentioning
confidence: 99%
“…Likewise the Wild Water Buffalo, Indian Bison and Bengal Florican showed narrow habitat choice. In the matrix analysis, swamps/marshes scored the highest species number with 15, followed by forest (14), river and lake (13) and grassland (12) and the least by agriculture (2). It was observed that forested ecosystems of the KTWR are one of the most important habitats used by 15 globally significant species followed by river and lakes and grassland.…”
Section: Distribution Pattern Of Threatened Speciesmentioning
confidence: 99%
“…By 2100, the impact of land use change on biodiversity is likely to be more significant than climate change, nitrogen deposition, species introductions and changing atmospheric concentrations of carbon dioxide on a global scale [10,11]. This has a strong implication on conservation and management of protected areas at global, regional and national levels, which are the store house and repository of a wide range of biodiversity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent information suggests that the Himalaya which forms the northern border of the Indian subcontinent is one of the most biodiversity rich regions on the earth. But sadly many of the taxa found here have been listed as critically threatened revealing the imminent threats posed to the wildlife of the region (Chettri et al 2010). The critically threatened species include Gharial Gavialis gangeticus, South Asian River Dolphin Platanista gangetica, Pygmy Hog Porcula salvania, several species of vultures, Bengal Florican Houbaropsis bengalensis, etc.…”
Section: Introductionmentioning
confidence: 94%